Baby grassland animals - Katirgis, Jane. (Berkeley Heights, NJ : Bailey Books, 2011)
Photographs and simple text profile some of the baby animals that are commonly found in a grassland.
Includes bibliographical references and index.
0.6
Preschool
Preschool
Keywords: Grassland animals -- Infancy -- Juvenile literature; Grassland animals; Animals -- Infancy; Animal babies; Grassland animals; Readers (Elementary)